Convergent Variation in the Leaf Traits of Desert Plants in the Ebinur Lake Basin - Nurbolat, Saltanat; Guanghui, Lv; Lamei, Jiang; Lei, Zhang (Frontiers in Environmental Science, 2022)
Elucidating the relationship between the variation of plant leaf functional traits and the environment is necessary for understanding the adaptation mechanism of plants and predicting changes in ecosystem structure. In this study, the leaf traits of desert plants in Ebinur Lake National Wetland Nature Reserve in Xinjiang, China were studied from the aspects of plant life forms (annuals, perennials and shrubs ), phylogenetic signals, and relation to soil properties, using the principal component analysis , variance decomposition, and one-way analysis of variance . The results showed that: (1) There were significant differences in leaf carbon concentration (annuals>shrubs>perennials), leaf nitrogen concentration (shrubs ≥ perennials ≥ annuals), and leaf moisture content (perennials ≥ annuals ≥ shrubs) among the life forms, but there was no significant difference in leaf phosphorus concentration. Besides, soil nitrogen and phosphorus were significantly positively correlated with leaf carbon concentration and leaf nitrogen concentration. (2) There were significant differences in leaf carbon concentration, leaf nitrogen concentration, specific leaf area, and leaf moisture content between C3 and C4 plants, while the differences in P and leaf dry matter content were not significant. Besides, there were significant differences in leaf carbon concentration, leaf nitrogen concentration, specific leaf area, and leaf moisture content between leguminous and non-leguminous plants. Leguminous plants had higher leaf carbon concentration, leaf nitrogen concentration, and specific leaf area than non-leguminous plants, while non-leguminous plants had higher leaf moisture content than leguminous plants. (3) One way ANOVA analysis showed that taxonomy had a more significant effects on leaf carbon concentration, leaf nitrogen concentration, specific leaf area, and leaf moisture content than soil properties, and the coefficient of variation of leaf carbon concentration was greater than 50%. The phylogenetically independent contrasts analysis showed that the phylogenetic signal of all leaf traits was detected in all species and low (K value <1, P >0.05), indicating that the functional traits were weakly affected by phylogenetics. Therefore, desert plants in the Ebinur Lake basin evolved to adapt to arid environments, and leaf traits showed convergent variation.